2009
DOI: 10.1007/s00158-009-0442-9
|View full text |Cite
|
Sign up to set email alerts
|

CAD based shape optimization for gas turbine component design

Abstract: In order to improve product characteristics, engineering design makes increasing use of Robust Design and Multidisciplinary Design Optimisation. Common to both methodologies is the need to vary the object's shape and to assess the resulting change in performance, both executed within an automatic loop. This shape change can be realised by modifying the parameter values of a suitably parameterised Computer Aided Design (CAD) model. This paper presents the adopted methodology and the achieved results when perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…According to the concept of Brujic et al, 26 the developed parameterization method is shown in Figure 3.…”
Section: Developed Parameterization Methods Of the Twdmentioning
confidence: 99%
“…According to the concept of Brujic et al, 26 the developed parameterization method is shown in Figure 3.…”
Section: Developed Parameterization Methods Of the Twdmentioning
confidence: 99%
“…There are articles in the literature that deal with the optimization of the fir tree root joint geometry with the objective of reducing the stresses in the joint. [16][17][18][19][20][21] Random errors in manufacturing process introduce variability in the geometry of the blade root and the disk slots. Due to the variability in blade and disk geometry within the tolerance limits, the contact area at joints could be higher or lower than that of the nominal design geometry.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Meguid et al studied the effect of variation in certain key geometric features of the fir tree, such as the number of teeth, flank angle, and flank length, on von‐Mises stresses on disk slot. There are articles in the literature that deal with the optimization of the fir tree root joint geometry with the objective of reducing the stresses in the joint …”
Section: Introductionmentioning
confidence: 99%
“…While such techniques succeed in automating the design process to some extent, thereby reducing both develop-FIGURE 1. A TRADITIONAL OPTIMIZATION WORKFLOW ment costs and time-to-market, some human interaction in the creation of such optimization workflows is unavoidable [4,5] and can be quite time consuming when developing a workflow to cope with complex topology changes.…”
Section: Introductionmentioning
confidence: 99%